Analysis of the Administration of State Property in the General Election Commission of North Sulawesi Province - Hizkia Tambingon; David Saerang; Rudy Pusung (International Journal of Business and Applied Economics, 2023)
Administration of State Property is a series of activities that include Bookkeeping, inventory, and Reporting. This study aims to find out whether the Administration of State Property at the General Election Commission of North Sulawesi Province is in accordance with the regulations governing the Administration of State Property. This research is a qualitative descriptive study with the data used in this study are primary data obtained from informants or informants as well as secondary data obtained from the literature. The results of this study indicate that the General Election Commission of North Sulawesi Province as the Accounting Unit for Proxy of Property Users (UAKPB) has carried out the process of administering State Property, but there are still some problems in carrying out administration, such as not having checked State Property in every room, and does not register construction in progress.